Ben Olsen on the art of flank play - Olsen, Ben; United Sports Training Center; Reedswain (firm) (Spring City, PA : Reedswain)
US National Team and DC United star, Ben Olsen, working with players from his alma mater FC Delco (Pa), demonstrates and coaches the art of flank play and the specific techniques required to excel in this all important area of attack
Title from title screen
Photos by Robyn Mcneil
Coacher: Ben Olsen
Keywords: Soccer -- Coaching; Soccer